Molecular-genetics analysis of 15 STR loci in sibship testing in isolated rural Bosnian population – the use of the grey zone - Jasmin Mušanović; Azra Metović; Esad Pepić; Almira Lujinović; Adnan Fojnica; Faruk Husremović; Damir Šečić; Damir Marjanović; Jasmin Šutković (Medicinski glasnik, 2023)
Aim: Examination of the effectiveness of STR loci in proving sibship of the Bosnian-Herzegovinian village of Orahovica and the formation of a “grey zone“. Methods: The probability of sibship was determined by calculating the likelihood ratio (LR) parameter for each of the 15 observed STR loci and for each of the pairs of relatives and non-relatives. Cumulative sibship index (CSI) was calculated for each of the pairs by multiplying the LR values of all 15 loci and obtained values are used as CSI limit for separating relatives from non-relatives. By creating a grey zone for local populations, an attempt was made to obtain a line of demarcation between siblings and non-siblings. Results: An analysis of the origin of the respondents' relatives was performed, up to the level of sibship in the third generation. The results of the CSI for pairs of relatives from the village of Orahovica showed that the highest CSI value, and therefore the sibship probability was recorded among relatives from the village of Orahovica (CSI=534211727.203;SP=99.999999812%). On the contrary, incredibly low CSI value was recorded among non-relatives, ranging from CSI=0.0000001 to 0.5261434 (SP=0.000009999% to 34.475357951%). Conclusion: For the threshold value CSI=1 and for CSI=3, this method determined sibship in 100% of pairs of relatives and the absence of biological sibship in 100% of pairs of non-relatives in the village of Orahovica. The STR system is proved to be a successful method in determining sibship or absence of sibship in small local populations.
Keywords: family; genetic testing; molecular diagnostic techniques; paternity